ANALISIS PENGELOLAAN ALOKASI DANA DESA BERBASIS VALUE FOR MONEY STUDI PADA DESA PINANG LUAR - Susanti, Lisa (ABDI EQUATOR, 2024)
The management of village fund allocation must ensure that every allocated rupee has a maximum impact on the development and welfare of the village community. The concept of "Value for Money" is a fundamental approach to assess the economy, efficiency, and effectiveness of village fund utilization. The goal of this research is to understand and analyze the financial performance of Pinang Luar Village for the fiscal years 2020-2022, considering economic, efficiency, and effectiveness aspects. The data analysis method used in this research is qualitative descriptive, which involves collecting, processing, and presenting the obtained data. This study measures the budget realization of Pinang Luar Village using three aspects: economic, efficiency, and effectiveness. Data collection methods include observation, interviews, and document studies. The results of the value-for-money-based measurement indicate that the financial performance of Pinang Luar Village in terms of the economy is categorized as economical and effective. However, in terms of efficiency, the financial performance of Pinang Luar Village is still categorized as inefficient from 2020 to 2022, primarily due to the carryover of budget surplus from the previous year. Additionally, Pinang Luar Village faces challenges in managing village fund allocations, attributed to three factors: unexpected costs, inefficient projects, and the introduction of new regulations.